Comparative Analysis of Supraorbital Eyebrow and Pterional Approaches for Cranio-Orbital Injury Management - Beksultan Yrysov, Tugolbai Tagaev, Keneshbek Yrysov, Aigul Ibraimova, Nelli Omurova, Aikanysh Oskonbaeva, Kurmanbek Dzheembaev, (Asian Journal of Pharmaceutics (AJP), 2025)
Cranio-orbital injuries are challenging craniofacial traumas because of the proximity of the orbital contents to vital neurovascular and ocular structures. Although the literature on orbital trauma is extensive, comparative evidence between the supraorbital eyebrow approach (SEA) and the pterional approach (PA) in traumatic cranio-orbital injuries remains limited, particularly in resource-constrained settings. Materials and Methods: This retrospective study evaluated the SEA and PA for treating cranio-orbital injuries in 49 patients who underwent 51 surgeries at a tertiary care center in Kyrgyzstan from 2014 to 2017. The main outcomes assessed were the degree of resection, visual function improvement, ptosis resolution, and proptosis reduction. Secondary outcomes included cosmetic satisfaction, post-operative complications, and functional recovery, as assessed using the modified Rankin Scale. Results: The SEA was used in 28 patients, whereas the PA was employed in 23 patients. The gross total resection rates were comparable between the two approaches. The SEA group reported higher cosmetic satisfaction and shorter incision lengths than the PA group (P < 0.05). Proptosis improved in 98.0% of cases, and visual function was enhanced in 63.2% of patients with pre-operative impairment. Ptosis resolved in most cases, with no significant differences between the surgical approaches used. At ≥12 weeks follow-up, 89.2% of patients attained a modified Rankin Scale score of <3, indicating independence in daily activities. Complications were infrequent, with no significant intergroup differences observed. Conclusion: The study suggests that The SEA is ideal for smaller anterior lesions, providing superior cosmetic results and lower morbidity, whereas the PA remains essential for larger or complex lesions requiring extensive exposure.